2013
DOI: 10.1371/journal.pone.0074863
|View full text |Cite
|
Sign up to set email alerts
|

Differential Host Response, Rather Than Early Viral Replication Efficiency, Correlates with Pathogenicity Caused by Influenza Viruses

Abstract: Influenza viruses exhibit large, strain-dependent differences in pathogenicity in mammalian hosts. Although the characteristics of severe disease, including uncontrolled viral replication, infection of the lower airway, and highly inflammatory cytokine responses have been extensively documented, the specific virulence mechanisms that distinguish highly pathogenic strains remain elusive. In this study, we focused on the early events in influenza infection, measuring the growth rate of three strains of varying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…We have previously observed that lung type I alveolar epithelial cells are rapidly infected in this experimental intranasal infection model, with faster kinetics than the descending infection that occurs during natural infection [20]. We observed a significantly lower viral load in type I epithelial cells isolated from miR-144/451-deficient mice relative to wild-type cells following in vitro influenza virus infection (Fig 2A).…”
Section: Resultsmentioning
confidence: 63%
“…We have previously observed that lung type I alveolar epithelial cells are rapidly infected in this experimental intranasal infection model, with faster kinetics than the descending infection that occurs during natural infection [20]. We observed a significantly lower viral load in type I epithelial cells isolated from miR-144/451-deficient mice relative to wild-type cells following in vitro influenza virus infection (Fig 2A).…”
Section: Resultsmentioning
confidence: 63%
“…In spite of the differential cytokine response, no major differences in immune cell infiltration were evident between H5N1 and H7N9 viruses. Recent studies have shown that early activation of NF-Band IL-17-mediated signaling pathways may substantially contribute to the development of severe disease (28), implying that the host cytokine/chemokine response may be just as crucial to disease outcome as viral load.…”
Section: Discussionmentioning
confidence: 99%
“…These whole-tissue transcriptomic analyses demonstrated that although the type I interferon transcriptional profiles of the 1918 and H5N1 viral strains were similar, genes related to the inflammatory response and cell death (including key components of the inflammasome, NLRP3, and IL-1β) were highly induced by the 1918 virus but were downregulated by the H5N1 strain (71). Similarly, we identified distinct transcriptional programs activated in the upper and lower airways by influenza strains of varying pathogenicity (72). Moreover, we determined that the induction of inflammation-related genes during swine-origin pandemic H1N1 infection in vitro is significantly delayed in comparison to infections with its parental strains (P. Dash, C.J.…”
Section: Systems Analysis Of Infectious Disease: Influenza As a Case mentioning
confidence: 99%